Comparison of C2-3 Pedicle Screw Fixation With C2 Spinous Muscle Complex and Iliac Bone Graft for Instable Hangman Fracture - Xu, Dingli; Gan, Kaifeng; Wang, Yang; Wang, Yulong; Ma, Weihu (Frontiers in Surgery, 2021)
Purpose To compare the effect between C2 spinous muscle complex graft and iliac bone graft in C2-3 pedicle screw fixation for instable Hangman fracture. Summary of Background Data. Using axial spinous muscle complex instead of iliac bone for instable Hangman fracture can decrease neck pain, bone donor site complication and operation time. Method The outcomes of C2-3 pedicle screw fixation with C2 spinous muscle complex were compared with iliac bone graft in 18 and 21 patients with instable Hangman fracture. The mean age was 49.1±15.8 years in the Complex group and 55.3±12.2 years in the Iliac group and the mean time to surgery of the patients was 3.3±0.6 days in the Complex group and 3.6±0.9 days in the Iliac group. Outcome measures including operation time, blood loss, visual analogue scale (VAS) for pain, Japanese orthopedic association score (JOA), American spine injure association classification (ASIA) and bone fusion time were collected from medical records. In addition, the postoperative complications were also recorded. Results There were significantly difference in operation time and interoperative blood loss between two groups(P<0.01). And significantly difference was found in VAS score and JOA score between two groups (P=0.0012 and P<0.001, respectively) at 1-month follow-up, whereas, no significantly difference was found at other visit time. At the final visit, all patients showed good bone fusion, and 2 patients shows incision edema and exudation in the iliac group. Conclusion C2-3 pedicle screw fixation with C2 Spinous Muscle Complex graft maybe a feasible and safe procedure for instable Hangman fracture.